Pentobarbital-induced lactic acidosis following status epilepticus barbiturate coma. (22nd February 2018) - Golden, Todd Rabkin; Solnicky, Veronika; Wadeea, Rita; Ghazala, Sehem
Abstract : We present a rare case of pentobarbital infusion causing propylene glycol-induced lactic acidosis, during refractory status epilepticus treatment in a 66-year-old man without seizure history.